Grass Flora from Plains of Radhapuram Taluk, Tirunelveli District, Tamil Nadu - Sekar, Ramarajan; Murugesan, A. G. (Indian Forester, 2017)
Within the wide diversity of flowering plants ’Grasses’ are the one which can be found anywhere with great abundance. Grasses are the members of Poaceae (Gramineae) family which are the most vital part in our life as food, medicine, cottage, as cattle-fodder and many different things. A total of 49 species based on different authentic floras have been compiled during the present study. Three species are endemic to Gulf of Mannar Biosphere Reserve.